Digital Inequality in GenAI tools utilised in EFL Learning contexts: Insights from Indonesian University Students - Purnama Cahya; Murdia (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study examines potential digital divides resulting from disparities between free and premium access to GenAI platforms among EFL students. Using a mixed-methods approach, data were collected through questionnaires consisting of Likert-scale and open-ended questions completed by 126 participants. Quantitative data were analysed using descriptive statistics and independent-samples t-tests, while qualitative responses were analysed thematically. Independent-samples t-tests found no statistically significant differences between the two access groups on any of the five variables (all p>.05), though small-to-moderate effect sizes emerged for AI usage (d = 0.42) and access perception (d = -0.45), suggesting students with both free and premium access tend to use GenAI tools somewhat more frequently, while free-only users tend to be more sensitive to access limitations. Effect sizes for perceived learning impact, fairness, and awareness of global inequality were negligible. Qualitative findings further indicate that effective GenAI use depends on prompting skills, critical thinking, and institutional guidance on ethical AI use and AI literacy training.